Livelihood adaptation and life satisfaction among land-lost farmers: Critiquing China’s urbanisation-driven land appropriation - Tong Weiming; Zhu Liyuan; Lo Kevin (Bulletin of Geography. Socio-Economic Series, 2019)
Large-scale rural land appropriation and displacement, driven by the unprecedented urban growth currently experienced in China, has created millions of land-lost peasants who live in the city but remain culturally, socially and institutionally rural. The situation has attracted growing attention in the literature because of its negative social impact, but relatively few studies have addressed how land-lost farmers adapt to urban ways of life and what factors influence their life satisfaction. In this paper, we investigate the predictors of livelihood adaptation and life satisfaction of land-lost farmers from a land appropriation case in the city of Changchun, Northeast China. The results show that, five years after the appropriation, livelihood adaptation remained very difficult and life satisfaction was poor among the resettlers. Furthermore, marginalised groups, such as those who were older, less educated and from smaller families, and those with lower pre-displacement income were less likely to have a higher income level after resettlement, resulting in a lower level of life satisfaction. Women also had lower life satisfaction than men. The study highlights an urgent need to improve China’s unjust land appropriation policy with a particular focus on attending to the needs of marginalised groups.